Loss Estimation for Kırşehir Province According to Different Earthquake Scenarios - Ercan Işık; Çoşkun Sağır; Zuhal Tozlu; Ümit Salim Ustaoğlu (Doğal Afetler ve Çevre Dergisi)
It is not possible to prevent earthquakes and to give notice in advance by using contemporary technological opportunities. However, it is possible to take precautions in order to minimize losses in case of an earthquake. Loss estimation models take a significant role in determining these precautions. Earthquake scenarios are used when preparing loss estimation models. The objective in earthquake scenarios is to estimate the economic losses, the damage to infrastructure, and the social impact associated with the potential earthquake. In this paper, it was discussed loss estimation models of three different earthquake scenarios developed for Kırşehir where is a seismically active province of Turkey. In the study, information about the seismicity of Kırşehir province was also given. Individual building damages, life and property losses and financial losses due to structural damage were obtained within each of the three earthquake scenarios. Building damages were calculated by two different methods which included in the software package. The greatest structural damage was observed in the Scenario 2 earthquake that is Akpınar Earthquake. The work has an important place in terms of modern disaster management and urban transformation. Such studies can be used as a support tool for decision makers at the pre-disaster preparation stage.